ADITIVOS ANTIBIÓTICO, PROBIÓTICO E PREBIÓTICO EM RAÇÕES PARA LEITÕES DESMAMADOS PRECOCEMENTE - Asdrubal Viana Santos; Elias Tadeu Fialho; Márcio Gilberto Zangerônimo; Vinícius de Souza Cantarelli; Tiago da Silva Teofilo; Juliano Pelição Molino (Ciência Animal Brasileira, 2016)
The objective of this study was to evaluate the addition of the prebiotic mannan oligosaccharide (MOS 0.2%), probiotic (Bacillus subtilis 30g/ton) and antibiotic (Bacitracin zinc 125g/ton) to piglets’ feed in the post-weaning phase. Eighty (Danbread x Agroceres) pigs were used, that is, 40 males and 40 females, with initial weight of 7.1 ± 0.0175 kg. A randomized block design was used with four treatments and five replicates: 1 - Control; 2 - Prebiotic; 3 - Probiotic; 4 - Antibiotic. The variables evaluated were average daily gain (ADG), daily feed intake (DFI), feed conversion (FC) fecal consistency and leukocyte count. At 43 days of age, the animals presented the same weight gain (P> 0.05); however, there was increased intake of the diet containing prebiotic (P> 0.05), and feed conversion was better for control diet (P <0 05). In the period of 54 days of age of the animals, there were no differences in daily weight gain (P> 0.05), daily feed intake (P> 0.05) and feed conversion (P> 0.05), and also no differences in fecal consistency (P> 0.05). The number of leukocytes increased at 32 days of age when the diets containing prebiotics and probiotics were used (P> 0.05). The diet containing prebiotics increased the number of monocytes (P <0.05), and the diet containing antibiotic provided greater number of basophiles (P <0.05) at 36 days of age. The number of lymphocytes was not altered by the experimental diets (P> 0.05), the diets promoted no changes in the immunoglobulins IgA, IgM and IgG (P> 0.05). The use of prebiotics, probiotics and antibiotics did not influence the animals’ performance from 22 to 54 days of age.